The Evolution of the IASC into the IASB, and the Challenges it Faces - Zeff, Stephen (The Accounting Review, 2012)
ABSTRACT: In this article, I undertake to review the major developments and turning-points in the evolution of the IASC, followed by the evolution of the IASB. At the conclusion, I suggest five challenges facing the IASB.